The Effect of Automated Systems on Revenue Collection in the Dar Rapid Transit Project in Tanzania - Ramadhani Nassoro; Robert Mashenene (International Journal of Management, Accounting and Economics)
The study evaluated the effects of automated systems on revenue collection within the Dar Rapid Transit (DART) project, focusing on cost reduction, revenue accuracy, and time allocation. Utilizing a cross-sectional design with a quantitative approach, the study targeted 1,200 employees, with a sample size of 114 determined through simple random sampling. Data were collected via structured questionnaires and secondary documentation, and analyzed using descriptive statistics, binary logistic regression and t-test with IBM SPSS software. Binary logistic regression results showed that cost reduction and revenue accuracy positively predicted higher revenue, while time allocation negatively impacted revenue. The study concluded that automated systems significantly enhanced cost efficiency, accuracy, and time management. Recommendations included investing further in system optimization, addressing time allocation inefficiencies, and engaging in regular evaluations and policy discussions to sustain improvements.